Distribution of the supremum of random processes from quasi-Banach $K_{σ}$-spaces - Kozachenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We study random processes from quasi-Banach $K_{σ}$-spaces of random variables whose domain of definition is not necessarily a compact set. We establish conditions under which the supremum of a properly normalized process belongs to the same space as the process itself. We also obtain estimates for the norm of this supremum.